2022
DOI: 10.1177/15589447221075667
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Loss of Reduction After Open Reduction and Internal Fixation of Isolated Olecranon Fractures in Adults

Abstract: Background: We sought to determine whether any relevant patient, fracture, surgical, or postoperative characteristics are associated with loss of reduction after plate fixation of isolated olecranon fractures in adults. Methods: Patients who underwent open reduction and internal fixation of an olecranon fracture at our institution over an 11-year period were analyzed. Electronic patient charts and radiographic images were reviewed to gather patient, fracture, surgical, and postoperative data. Statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…In a study of 321 olecranon fractures fixed with precontoured PO, 15.6% patients underwent implant removal 72 . This study has shown that reoperations occur more in young patients and in more complex fractures including Mayo type 3 and Monteggia-like fractures 47,72-74 . Two comparative studies compared different types of PO and showed comparative functional outcomes and reoperations regardless of the type of plate used 30,75-78 .…”
Section: Plate Osteosynthesismentioning
confidence: 70%
“…In a study of 321 olecranon fractures fixed with precontoured PO, 15.6% patients underwent implant removal 72 . This study has shown that reoperations occur more in young patients and in more complex fractures including Mayo type 3 and Monteggia-like fractures 47,72-74 . Two comparative studies compared different types of PO and showed comparative functional outcomes and reoperations regardless of the type of plate used 30,75-78 .…”
Section: Plate Osteosynthesismentioning
confidence: 70%
“… 4 Forced reduction may result in the formation of “steps” on the articular surface, leading to postoperative traumatic arthritis. 5 In cases with extensive fracture defects, bone resorption at the fractured end can result in nonunion. 6 - 8 Although autogenous bone grafts have the potential to restore ulnar length, their use is limited by the high technical demands involved.…”
Section: Introductionmentioning
confidence: 99%
“…However, the apparent simplicity of the fracture does not equate to uneventful fixation. In my experience, an olecranon fragment of small size, especially in the presence of osteoporosis, may not be adequately stabilized with a plate and screw construct, and this was recently highlighted by Contreras et al [2].…”
mentioning
confidence: 99%
“…The extended plate has a long proximal part that curves around the olecranon toward the tip, thereby decreasing the distance between the olecranon tip and the most proximal screw (Fig. 2), which has been shown to reduce loss of reduction [2]. Moreover, the extended proximal part allows insertion of two additional 3.5-mm locking screws which, in a small osteoporotic metaphyseal bone fragment, can greatly enhance fixation [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation